Perceptions about the development of Black South African languages for use in basic education in South Africa - Mabela, Lefty; Ditsele, Thabo (South African Journal of African Languages, 2024)
The development of Black South African languages (BSALs) has been a subject of discussion for indigenous languages activists. This development was deemed necessary in basic education, hence our research targeted parents and guardians of the learners. The study assessed the perceptions of parents and guardians about the development and use of BSALs in basic education. Qualitative and quantitative data were collected through a questionnaire and Likert scale. That was done to investigate the awareness of parents and guardians about their freedom to choose a language of their choice for learning and their perception and attitudes about the use and development of BSALs in basic education. The survey revealed, among other things, that parents and guardians preferred English for their children to BSALs, although they accepted that these languages are also important for identity and culture maintenance. Furthermore, the notion of monolingual education was rejected. It was also discovered that they thought mother tongue education would deprive their children of socio-economic mobility. Moreover, the respondents expressed that BSALs are not developed and promoted enough by the government. These findings led the researchers to conclude that the parents and guardians value English in education for the power, status and opportunities it presents, while BSALs should be in the system to preserve culture and identity.